Utilizing Let’s Read Asia Website to Enhance Students’ Reading Comprehension in Descriptive Text - Cici Tiara Dewi (Indonesian Journal Publisher, 2026)
The aim of this study is to determine the effectiveness of the Let’s Read Asia website to be applied for improving Junior High School students’ comprehension in reading descriptive texts. A quantitative method through a quasi-experimental design was applied to 60 seventh grade students from a school in Surabaya, Indonesia. The data collection method was incorporated through writing tests prior and following the treatment that assessed aspects of understanding adjectives and meanings in descriptive texts. The data obtained were analyzed using an independent sample t-test with the purpose of determining differences that were statistically significant and using effect size calculations to assess the magnitude of the effect of the platform. The result demonstrated a notable increase in the pre-test average score of 61.83 and the post-test score of 81.67, indicating that the platform can be used to improve reading skills in descriptive texts. The independent sample t-test for the experimental class revealed a statistically significant difference. The media usage is demonstrated to have a large effect on the learning process. Findings highlight the benefit of the platform for further enhancing students’ ability in reading.